Phosphor plate
Patent Information
- Application Number
- JP2023130941
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-10
- Publication Date
- 2025-02-21
AI Technical Summary
【0010】 本発明によれば、白色光LED、白色光LDにおいて、より高い光束が得られる蛍光体プレートを提供することができる。
Smart Images

Figure 2025025806000002 
Figure 2025025806000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a ceramic phosphor plate that obtains white light by converting the wavelength of light emitted from a light emitting diode (LED) or a laser diode (LD). [Background technology]
[0002] White light LEDs and white LDs have a longer life span and lower power consumption than fluorescent lamps, and as such are increasingly being used as illumination sources in backlights and display panels for small displays, panels for large displays, car headlamps, and other general lighting fixtures.
[0003] Among the methods for achieving white light with LEDs and LDs, the most promising application, particularly in lighting fixtures such as car headlights that require higher heat resistance and durability, is the combination of blue LED or LD chips with various ceramic phosphors. When a blue LED is used as the light-emitting element, the light emitted from the blue LED excites the yellow phosphor in the ceramic phosphor, and white light is emitted by additively mixing the blue and yellow colors.
[0004] As such a ceramic phosphor, for example, Patent Document 1 describes a phosphor plate that emits white light with a large luminous flux, suppresses the decrease in luminous efficiency due to temperature rise, and has a small chromaticity difference, as shown in (Y 1-x-y ,Gd x ,Ce y )3AlO 12 The sintered body is made of Al2O3 particles (where 0.07≦x≦0.11, 0.010≦y≦0.015) and Al2O3 particles, (Y 1-x-y ,Gd x ,Ce y )3AlO 12 The average particle size of the particles is 4 μm or more and 6 μm or less, (Y 1-x-y ,Gd x ,Ce y )3AlO 12 For a total of 100 vol% of the particles and Al2O3 particles, (Y1-x-y ,Gd x ,Ce y )3AlO 12 The particle concentration is 20 vol% or more and 30 vol% or less, and the average particle size of the Al2O3 particles and (Y 1-x-y ,Gd x ,Ce y )3AlO 12 The ratio of the average particle size of the particles (Al2O3 / (Y 1-x-y ,Gd x ,Ce y )3AlO 12 ) is 1 or more and 2 or less, and the total thickness of the fired body is 150 μm or more and 250 μm or less.
[0005] In addition, as an example of providing an anti-reflection film on a wavelength conversion layer to improve reliability and light extraction efficiency, Patent Document 2 discloses a wavelength conversion element having a wavelength conversion layer that converts light of a first wavelength to light of a second wavelength, a planarization layer having a surface roughness smaller than that of the wavelength conversion layer on at least one surface of the wavelength conversion layer, and an anti-reflection film that prevents reflection of at least a part of the light of the first wavelength or the light of the second wavelength on the planarization layer. Patent Document 2 describes that the surface roughness Ra of the planarization layer is preferably 100 nm (0.1 μm) or less, more preferably 10 nm (0.01 μm) or less, and even more preferably 5 nm (0.005 μm) or less, and discloses that by having such a planarization layer on the surface of the wavelength conversion layer made of a sintered phosphor, the voids on the surface of the wavelength conversion layer are filled with the planarization layer, and an anti-reflection film that matches the refractive index of the planarization layer can be formed, thereby improving light utilization efficiency. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2022-104527 A [Patent Document 2] JP 2022-41839 A Summary of the Invention [Problem to be solved by the invention]
[0007] In recent years, various studies have been conducted on the improvement of LED chips, LD chips, and phosphor materials in order to increase the luminous flux of white light LEDs and white light LDs even if only slightly. Although the phosphor plate described in the above-mentioned Patent Document 1 has certainly improved the luminous flux to a certain extent, it has not fully met the recent demands. In this context, the present invention aims to provide a phosphor plate that can obtain a higher luminous flux in white light LEDs and white light LDs. [Means for solving the problem]
[0008] The phosphor plate of the present invention is a phosphor plate comprising a plate-shaped fired body having a light incident surface that receives light from a light source and a light exit surface that is disposed opposite to the light incident surface and that emits the light received at the light incident surface, a glass coating layer formed on at least the light exit surface of the fired body, and an anti-reflection film further formed on the glass coating layer, wherein the fired body has a thickness of (Y 1-x-y ,Gd x ,Ce y )3AlO 12 particles (wherein 0.018≦x≦0.054 and 0.018≦y≦0.023) and Al2O3 particles, 1-x-y ,Gd x ,Ce y )3AlO 12 the overall average particle size of the Al2O3 particles is 3.0 μm or more and 5.0 μm or less, the overall thickness of the fired body is 90 μm or more and 160 μm or less, the glass coating layer is formed of an inorganic glass coating material, and the surface roughness Ra of the glass coating layer surface is 0.02 μm or more and 0.2 μm or less.
[0009] The phosphor plate of the present invention is 1-x-y ,Gd x ,Ce y )3AlO 12 For a total of 100 vol% of the particles and Al2O3 particles, (Y1-x-y ,Gd x ,Ce y )3AlO 12 The particle concentration is preferably 15 vol % or more and 25 vol % or less. Effect of the Invention
[0010] According to the present invention, it is possible to provide a phosphor plate that can provide a higher luminous flux in a white light LED or a white light LD. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a diagram showing a phosphor plate according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The phosphor plate of the present invention will be described in detail below with reference to the drawings. The phosphor plate 1 of the present invention comprises a plate-shaped fired body 6 having a light incident surface 2 that receives light from a light source and a light exit surface 3 that is arranged opposite the light incident surface 2 and exits the light received by the light incident surface 2, a glass coating layer 4 formed on at least the light exit surface 3 of the fired body 6, and an anti-reflection film 5 further formed on the glass coating layer 4.
[0013] The plate-shaped fired body 6 of the phosphor plate 1 is (Y 1-x-y ,Gd x ,Ce y )3AlO 12 particles (hereinafter also referred to as "YAG-based particles") and Al2O3 particles, 1-x-y ,Gd x ,Ce y )3AlO 12The overall average particle size of the Al2O3 particles and the Al2O3 particles is 3.0 μm or more and 5.0 μm or less, and x and y in the YAG particles are adjusted to 0.018≦x≦0.054 and 0.018≦y≦0.023. With good internal light scattering due to the fired body made of such a composite material and having the specific overall average particle size, the Ce concentration (y) in the YAG particles is made higher than in the conventional technology and the Gd concentration (x) is made lower than in the conventional technology, thereby increasing the conversion efficiency from blue light to yellow light and reducing the overall thickness of the fired body 6 to 90 μm or more and 160 μm or less, and as a result, the luminous flux can be increased compared to the conventional technology.
[0014] The above (Y 1-x-y ,Gd x ,Ce y )3AlO 12 When the overall average particle size of the Al2O3 particles is 3.0 μm to 5.0 μm, and the overall thickness of the fired body 6 is 90 μm to 160 μm, if y is less than 0.018 and x is more than 0.054, the conversion efficiency from blue light to yellow light is low, resulting in a bluish white color. If y is more than 0.023 and x is less than 0.018, the color is yellowish white.
[0015] By making the YAG particles have a range of 0.018≦x≦0.054 and 0.018≦y≦0.023, making the overall average particle size of the YAG particles and the Al2O3 particles 3.0 μm or more and 5.0 μm or less, and making the overall thickness of the fired body 6 90 μm or more and 160 μm or less, it is possible to achieve a white color with little other coloring (high whiteness) and to increase the luminous flux.
[0016] In particular, by setting x to 0.054 or less and reducing the amount of Gd that causes high-temperature degradation, the temperature characteristics can be improved. The temperature characteristics refer to the temperature dependency of the wavelength conversion efficiency, and the deterioration of the temperature characteristics refers to the decrease in the wavelength conversion efficiency with an increase in temperature. In the phosphor plate of the present invention, the Gd / Ce content ratio in the phosphor plate is preferably 0.9 to 2.2, inclusive, because a phosphor plate with a higher whiteness can be obtained by setting the ratio in this range.
[0017] Here, the temperature characteristics were calculated by placing the phosphor plate 1 (10 mm x 10 mm) in the center of a 4-inch integrating sphere equipped with a heater, irradiating it with excitation light of 450 nm ± 1 nm in the same manner as in measuring the fluorescence wavelength, measuring the quantum efficiency at 25°C and 200°C from the emission spectrum of phosphor plate 1, and dividing the quantum efficiency at 200°C by the quantum efficiency at 25°C.
[0018] If the overall average particle size of the YAG particles and the Al2O3 particles is less than 3.0 μm, there will be too many grain boundaries and sufficient luminous flux will not be obtained, and if it exceeds 5.0 μm, sufficient internal light scattering will not be obtained in the overall thickness of the fired body, resulting in low conversion efficiency from blue light to yellow light and a bluish white color.
[0019] If the total thickness of the fired body 6 is less than 90 μm, sufficient internal light scattering cannot be obtained, the efficiency of conversion from blue light to yellow light is low, and the color becomes bluish white, whereas if it exceeds 160 μm, sufficient luminous flux cannot be obtained.
[0020] In addition, in the plate-shaped sintered body 6, the (Y 1-x-y ,Gd x ,Ce y )3AlO 12 The Gd content x and the Ce content y in the particles can be measured by ICP atomic emission spectrometry.
[0021] The overall average particle size of the YAG particles and the Al2O3 particles can be measured by photographing the particles using a laser microscope or a scanning electron microscope and using a linear intercept method. At this time, the grain boundaries can be observed more clearly by performing thermal etching as necessary.
[0022] Furthermore, the total thickness of the sintered body 6 can be measured with a micrometer or by standing the sintered body upright and observing it with an optical microscope.
[0023] In this specification, luminous flux refers to the brightness of white light, and refers to the brightness of white light produced by additive color mixing when a blue LED chip is mounted in a light-emitting device and the blue LED is irradiated onto the phosphor plate 1 to cause it to emit fluorescent light.
[0024] The phosphor plate 1 of the present invention has a structure in which a glass coating layer 4 is formed on at least the light exit surface 3 of the fired body 6, and an anti-reflection film 5 is further formed on the glass coating layer. The fired body has a large number of fine irregularities on its surface, which causes the emitted light to be scattered significantly and radiated at various angles. For this reason, if the anti-reflection film 5 is provided directly on the surface of the fired body 6, the light will be incident on the anti-reflection film 5 at various angles, and the function of the anti-reflection film will not be fully exhibited. Therefore, in order to reduce light scattering, in the present invention, a glass coating layer 4 with a suitable surface roughness is formed on at least the light exit surface 3 of the fired body 6.
[0025] The surface roughness Ra (based on JIS B 0601:1994) of the surface of the glass coating layer 4 is 0.02 μm or more and 0.2 μm or less. Patent Document 2 describes that it is preferable that the surface roughness Ra of the planarization layer formed on one side of the wavelength conversion element is as small as possible, but in a very flat surface with Ra of less than 0.02 μm, the difference between the yellow light and the blue light emitted from the surface of the antireflection film 5 formed on the upper surface of the planarization layer is large, resulting in a bluish white color.
[0026] For this reason, in the present invention, an appropriate roughness is provided to the glass coating layer 4 to prevent a decrease in whiteness (the smaller the deviation from the CIE chromaticity coordinates (0.33, 0.33), the higher the whiteness). In the present invention, by setting the surface roughness Ra of the glass coating layer surface to 0.02 μm or more and 0.2 μm or less, the function of the antireflection film 5 can be fully exhibited, and the CIE chromaticity coordinates of white light emitted from the surface of the antireflection film 5 can be made to approach (0.33, 0.33).
[0027] The glass coating layer 4 is formed of an inorganic glass coating material. The inorganic glass coating material is, for example, perhydropolysilazane, which is a polymeric compound that does not contain carbon compounds such as methyl groups or vinyl groups in its side chains. A glass coating layer formed of an organic glass coating material has low wettability and poor adhesion to the anti-reflection film 5, and localized peeling of the anti-reflection film 5 occurs in a post-process (cutting, cleaning, inspection, etc.), or if the peeling does not occur, microvoids are formed at the interface between the glass coating layer and the anti-reflection film, resulting in a failure to obtain a high luminous flux. In contrast, by using an inorganic glass coating material, a tight anti-reflection film without microvoids is formed at the interface with the anti-reflection film, and a high luminous flux is obtained.
[0028] The fact that the glass coating layer is made of an inorganic glass coating material can be confirmed by the value of the C / Si molar ratio obtained by analyzing the cross section by energy dispersive X-ray analysis (EDS). When an organic glass coating material such as organopolysiloxane is used, the C / Si molar ratio is 5 or more, whereas when an inorganic glass coating agent such as perhydropolysilazane is used, the C / Si molar ratio is 1 or less, even including measurement errors such as when carbon tape is used to fix the sample in the EDS analysis and contamination such as hydrocarbons.
[0029] The average thickness of the glass coating layer is preferably 0.3 μm to 3 μm, more preferably 0.5 μm to 2 μm, which can provide a more uniform surface roughness of the glass coating layer and reduce color unevenness.
[0030] For example, spin coating can be used as a method for forming the glass coating layer 4. In the spin coating method, a sintered body onto which perhydropolysilazane (PHPS) dissolved in an organic solvent is dropped is rotated at high speed to form a uniform polysilazane layer over the entire surface of the substrate, and then a heat treatment (baking) is performed at 400 to 500°C in an oxidizing atmosphere to obtain a dense glass coating film.
[0031] The antireflection film 5 is preferably a dielectric multilayer film, more preferably a dielectric multilayer film made of two or more materials with different refractive indices, and more preferably has an antireflection function against light with a wavelength of 400 to 800 nm. A specific example is a laminate film in which silicon dioxide (SiO2) films and tantalum (V) oxide (Ta2O5) films, each having a thickness of 10 nm to 100 nm, are alternately laminated in 3 to 10 layers so that the total thickness is 800 nm or less. In the laminate film, the wavelength range in which the antireflection function is exerted can be adjusted by changing the thickness of each film or the number of layers. In the present invention, in addition to antireflection films that are effective in the entire visible light range, dielectric multilayer films that have the effect of transmitting specific wavelengths, such as dichroic filters, bandpass filters, and notch filters, are also considered to be part of the antireflection film. In such dielectric multilayer films, for example, tantalum (V) oxide (Ta2O5), titanium (IV) oxide (TiO2), niobium (V) oxide (Nb2O5), etc. are used as high refractive index materials, and silicon dioxide (SiO2), magnesium fluoride (MgF2), etc. are used as low refractive index materials.
[0032] The total thickness of the antireflection film 5 is preferably 100 nm or more and 1000 nm or less, and more preferably 300 nm or more and 800 nm or less, in order to provide a more excellent antireflection function for a specific wavelength.
[0033] The anti-reflection film 5 may be formed not only on the light exit surface 3 but also on the light entrance surface 2. This reduces the reflection of the blue LED light incident on the phosphor plate 1 and improves the capture efficiency, thereby increasing the conversion efficiency and the extraction efficiency, and as a result, the luminous flux of the emitted light can be further increased.
[0034] In the fired body 6 in the phosphor plate 1 of the present invention, the concentration of the YAG particles is preferably 15 vol% or more and 25 vol% or less with respect to the total amount of the YAG particles and Al2O3 particles being 100 vol%. By setting the concentration of the YAG particles in the above range, the internal light scattering in the fired body can be made more appropriate. The concentration of the YAG particles can be determined by calculating the ratio of the YAG phase to the Al2O3 phase by X-ray diffraction (XRD) of the phosphor plate 1.
[0035] An example of a method for producing the phosphor plate 1 of the present invention will be described below. Yttrium oxide (III) (Y2O3), cerium oxide (IV) (CeO2), gadolinium oxide (III) (Gd2O3) and aluminum oxide (Al2O3) are mixed and formed into a sheet, which is then degreased and pressed to create a green molded product of a desired shape. Next, the green molded product is cut into 1.0 x 10 -2 A fired body is obtained by firing under a vacuum atmosphere of about medium to low vacuum of not more than Pa. The fired body is a sintered body made of YAG particles and Al2O particles.
[0036] Next, the surface of the fired body 6 is glass-coated. As described above, the glass coating is performed using a method such as spin coating. Next, an anti-reflection film 5 is formed on the fired body that has been surface-treated by glass coating. When the above-mentioned dielectric multilayer film is formed as the anti-reflection film 5, SiO2 films and Ta2O5 films are alternately laminated using a film formation method such as vacuum deposition, ion plating, sputtering, and chemical vapor deposition (CVD). EXAMPLES
[0037] The present invention will be described in detail below based on examples, but the present invention is not limited to the examples shown below. [Example 1] [Preparation of Chip Phosphor Plate] [1][(Y 1-x-y ,Gd x,Ce y )3AlO 12 +Al2O3] sintered body Cerium (IV) oxide powder with an average particle size of 0.4 μm and a purity of 99.9%, yttrium (III) oxide powder with an average particle size of 1.0 μm and a purity of 99.9%, gadolinium (III) oxide powder with an average particle size of 0.7 μm and a purity of 99.9%, and aluminum oxide powder with an average particle size of 0.3 μm and a purity of 99.9% were mixed in a predetermined blending ratio to obtain a raw material powder. 1-x-y ,Gd x ,Ce y )3AlO 12 The weights of the yttrium (III) oxide powder, gadolinium (III) oxide powder, cerium (IV) oxide powder and aluminum oxide powder were adjusted so that the Gd concentration and Ce concentration in the sintered body (+Al2O3) would be the compositions shown in Table 1.
[0038] Ethanol, polyvinyl butyral (PVB)-based binder, and succinic acid-based plasticizer were added to this raw material powder, and the mixture was ground and mixed for 50 hours in a ball mill using aluminum oxide balls to prepare a slurry. This slurry was used to form green sheets of a predetermined thickness by the doctor blade method. At this time, the thickness and number of layers of the green sheets to be formed were adjusted so that the resulting fired body had the thickness shown in Table 1. Specifically, an 80 μm green sheet was prepared and two of these were laminated. The obtained green sheet (laminate) was degreased in air, calcined, and then cooled to 1.0 × 10 -2 The mixture was fired at 1680°C in a vacuum atmosphere of 0.01 Pa or less, and (Y 1-x-y ,Gd x ,Ce y )3AlO 12 The sintered body consisting of ZnO particles and Al2O3 particles was obtained.
[0039] [2] Formation of a glass coating layer on the surface of the fired body A mixed solution of perhydropolysilazane and dibutyl ether (Sanwa Chemical Sancerazane ANN120-20) was uniformly applied to the surface of the fired body by spin coating, and then baked at 450°C to form a glass coating layer with a thickness of 1.5 μm on the surface of the fired body.
[0040] [3] Formation of an anti-reflective coating on the glass coating layer Using a vacuum deposition method, an anti-reflective film (dielectric multilayer film) was formed by alternately depositing Ta2O5 and SiO2, with the layer in contact with the glass coating layer being Ta2O5 and the top layer being SiO2, with each layer being 50 nm thick so that the total thickness was 500 nm.
[0041] [4] Disconnect The fired body having the glass coating layer and the anti-reflection film formed thereon was cut into 1 mm square by dicing to produce chip-shaped phosphor plates.
[0042] [Evaluation of Chip Phosphor Plates] [1] Gd and Ce concentrations The (Y 1-x-y ,Gd x ,Ce y )3AlO 12 The Gd and Ce concentrations in the sintered body consisting of the particles and Al2O3 particles were determined.
[0043] [2](Y 1-x-y ,Gd x ,Ce y )3AlO 12 Particle concentration The ratio of the YAG phase to the Al2O3 phase was calculated by X-ray diffraction (XRD) of the phosphor plate. 1-x-y ,Gd x ,Ce y )3AlO 12 The total amount of Al2O3 particles and Y 1-x-y ,Gd x ,Ce y )3AlO 12The particle concentration was measured, and the result was 20 vol % in all of the Examples and Comparative Examples.
[0044] [3] Room temperature luminous flux The chip-shaped phosphor plate was fixed on a blue LED element (light-emitting area 1 mm square, light-emitting wavelength 450 nm) with silicone resin. After collecting the light emitted with a 4-inch integrating sphere, the emission spectrum at room temperature was measured using a visible-near infrared fiber multichannel spectrometer (manufactured by Ocean Photonics, product name USB4000-VIS-NIR-ES). The luminous flux was calculated from the obtained emission spectrum. The relative luminous flux was calculated by taking the luminous flux of the same type of LED sealed with 20 vol% of commercially available YAG:Ce phosphor powder (Mitsubishi Chemical Chemical High-Technica, product name P46-Y3) impregnated in commercially available phenyl silicone resin (Dow Corning, product name OE-6630) as 100. When the relative luminous flux value was 127 or more, bright white light was obtained, and when it was 121 or less, it was determined to be insufficient.
[0045] [4] Temperature characteristics The chip-shaped phosphor plates were arranged in three rows, three columns, and three diagonals into a 3 x 3 chip using commercially available phenyl silicone (Dow Corning, product name OE-6630) resin, and placed in the center of a 4-inch integrating sphere equipped with a heater. As in the case of measuring the fluorescence wavelength, excitation light of 450 nm ± 1 nm was irradiated, and the quantum efficiency at 25°C and 200°C was measured from the emission spectrum of the phosphor plate. The quantum efficiency at 200°C was divided by the quantum efficiency at 25°C to determine the temperature characteristic. A quantum efficiency of 84 or more was judged to be excellent in terms of temperature dependency of wavelength conversion efficiency, and a quantum efficiency of 81 or less was judged to be inferior.
[0046] [5] Whiteness The chip-shaped phosphor plate was fixed on top of a blue LED element (light-emitting area 1 mm square, light-emitting wavelength 450 nm) with silicone resin. The chromaticity (CIE_x, CIE_y) of the light emitted from the phosphor plate in the vertical direction (0°) in the CIE 1931 color space was measured. When ΔCIE_x and ΔCIE_y were both 0.02 or less for the white chromaticity (0.33, 0.33), the whiteness was judged to be excellent, and when it was greater than 0.02, it was judged to be poor.
[0047] [comprehensive evaluation] If all of the evaluation items [3] to [5] were excellent, they were marked with an "O"; if there was even one poor value, they were marked with a "△"; and if there were two or more poor values, they were marked with an "X." The results are shown in Table 1.
[0048] [Examples 2 and 3] [Comparative Examples 1 and 2] A chip-shaped phosphor plate was produced in the same manner as in Example 1, except that the composition of the raw material powder (gadolinium (III) oxide powder concentration, cerium (IV) oxide powder concentration) was changed and the Gd concentration and Ce concentration of the fired body were changed as shown in Table 1. (Y 1-x-y ,Gd x ,Ce y )3AlO 12 The composition of the sintered body consisting of Al2O3 particles and Al2O3 particles was adjusted as shown in Table 1. The composition of the phosphor plate and the results of evaluation in the same manner as in Example 1 are shown in Table 1. It was found that Comparative Example 1, which had a high Ce concentration, had a small room temperature luminous flux and was inferior in white light brightness, while Comparative Example 2, which had a high Gd concentration, had poor temperature dependence of wavelength conversion efficiency (luminous flux at high temperatures) from room temperature to 200°C.
[0049] [Examples 4 to 6] [Comparative Examples 3 and 4] A phosphor plate was produced in the same manner as in Example 1, except that the thickness of the green sheet formed by the doctor blade method was changed and the thickness of the fired body was changed as shown in Table 1. The composition of the phosphor plate and the results of evaluation in the same manner as in Example 1 are shown in Table 1. In Comparative Example 3, in which the fired body was thin, bright white light was obtained, but the whiteness was poor, whereas in Comparative Example 4, in which the fired body was thick, the brightness was poor.
[0050] [Examples 7 and 8], [Comparative Examples 5 and 6] A phosphor plate was produced in the same manner as in Example 1, except that the firing temperature was changed and the overall average particle size of the fired body was changed as shown in Table 1. The composition of the phosphor plate and the results of evaluation in the same manner as in Example 1 are shown in Table 1. In Comparative Example 5, in which the fired body had a small overall average particle size, sufficient luminous flux was not obtained. On the other hand, in Comparative Example 6, in which the fired body had a large overall average particle size, sufficient internal light scattering was not obtained, the conversion efficiency from blue light to yellow light was low, and the color was bluish white.
[0051] [Comparative Example 7] In Comparative Example 7, a phosphor plate was prepared in the same manner as in Example 1, except that the raw materials used to form the glass coating layer were changed from perhydropolysilazane, an inorganic glass coating material, to organopolysilazane, an organic glass coating material. The composition of the phosphor plate and the results of evaluation in the same manner as in Example 1 are shown in Table 1. In Comparative Example 7, in which the glass coating layer was formed using organopolysiloxane, an organic glass coating material (the C / Si molar ratio in the cross section was 7.0), localized peeling occurred in the anti-reflective film (localized voids at the interface between the glass coating layer and the anti-reflective film / cross-sectional SEM observation results), and the brightness of white light was inferior.
[0052] [Comparative Example 8] A phosphor plate was produced in the same manner as in Example 1, except that the above spin coating was repeated three times. The composition of the phosphor plate and the results of evaluation in the same manner as in Example 1 are shown in Table 1. In Comparative Example 8, in which the surface roughness Ra of the glass coating layer surface was small, the color was slightly bluish white.
[0053] [Example 9] A phosphor plate was produced in the same manner as in Example 1, except that the above spin coating was repeated twice. The composition of the phosphor plate and the results of evaluation in the same manner as in Example 1 are shown in Table 1. The phosphor plate of this Example 9, in which the surface roughness Ra of the glass coating layer surface was 0.020, larger than the 0.010 of Comparative Example 8, had high room temperature luminous flux, good temperature characteristics, and high whiteness, similar to the other Examples.
[0054] [Example 10] A phosphor plate was produced in the same manner as in Example 1, except that the ratio of perhydropolysilazane in the mixed solution of perhydropolysilazane and dibutyl ether was set to 2 / 3. The composition of the phosphor plate and the results of evaluation in the same manner as in Example 1 are shown in Table 1. The phosphor plate of this Example 10, in which the surface roughness Ra of the glass coating layer surface was 0.200, which was smaller than the 0.210 of Comparative Example 9, had high room temperature luminous flux, good temperature characteristics, and high whiteness, similar to the other Examples.
[0055] [Comparative Example 9] A phosphor plate was produced in the same manner as in Example 2, except that the ratio of perhydropolysilazane in the mixed solution of perhydropolysilazane and dibutyl ether was halved. The composition of the phosphor plate and the results of evaluation in the same manner as in Example 1 are shown in Table 1. In Comparative Example 9, in which the surface roughness Ra was greater than 0.020, the emitted light was largely scattered, and the luminous flux was insufficient.
[0056] [Comparative Example 10] A phosphor plate was produced in the same manner as in Example 2, except that an anti-reflection film was not formed. The composition of the phosphor plate and the results of evaluation in the same manner as in Example 1 are shown in Table 1. In this Comparative Example 10, the brightness of the white light was insufficient.
[0057] [Reference example] As a conventional example, ((Y 1-x-y ,Gd x ,Ce y )3AlO 12 +Al2O3) (x=0.070; y=0.012) fired body was used to prepare a phosphor plate having a thickness of 200 μm without providing a glass coating or an anti-reflection film, and the plate was evaluated in the same manner as in Example 1. As shown in Table 1, the phosphor plate of the reference example was inferior to the phosphor plate of the present invention in both room temperature luminous flux and temperature characteristics.
[0058] The above experiments confirmed that the phosphor plate of the present invention can provide a higher luminous flux and excellent whiteness in a white light LED.
[0059] [Table 1] [Explanation of symbols]
[0060] 1 Phosphor plate 2 Light incidence surface 3 Light exit surface 4 Glass coating layer 5 Anti-reflection coating 6. Baked body (phosphor layer)
Claims
1. A plate-shaped fired body having a light incident surface that receives light from a light source and a light exit surface that is disposed opposite the light incident surface and that emits the light received at the light incident surface; A phosphor plate having a glass coating layer formed on at least the light emitting surface of the fired body, and an anti-reflection film further formed on the glass coating layer, The fired body is (Y 1-x-y , Gd x , Ce y ) 3 A 5 O 12 particles (wherein 0.018≦x≦0.054 and 0.018≦y≦0.023) and Al 2 O 3 It consists of particles, The (Y 1-x-y , Gd x , Ce y ) 3 A 5 O 12 Particles and the Al 2 O 3 The particles have an overall average particle size of 3.0 μm or more and 5.0 μm or less, The total thickness of the fired body is 90 μm or more and 160 μm or less, The glass coating layer is formed of an inorganic glass coating material, and the surface roughness Ra of the glass coating layer is 0.02 μm or more and 0.2 μm or less.
2. The (Y 1-x-y , Gd x , Ce y ) 3 A 5 O 12 Particles and Al 2 O 3 With respect to the total amount of particles being 100 vol%, (Y 1-x-y , Gd x , Ce y ) 3 A 5 O 12 2. The phosphor plate according to claim 1, wherein the concentration of the particles is 15 vol % or more and 25 vol % or less.
Citation Information
Patent Citations
Wavelength conversion element, light source device, image projector, and method for manufacturing wavelength conversion element
JP2022041839A
Phosphor plate
JP2022104527A